(untitled) (Comparatismi, 2020)
The article focuses on the recent perspectives of thematic and myth criticism, by analyzing the methodological risks they have to face (the contentism and the indiscriminate accumulation of materials), and by proposing a model of transmedial comparativism which could revitalize the classic approach of inter artes studies. In the last part, the article, which also focuses on the idea of mode as a set of formal and thematic traits, discusses the example of Don Giovanni, a modern myth strictly connected with the theme of seduction and with a lot of philosophical and anthropological implications.